1999
DOI: 10.1023/a:1006155723059
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A cDNA encoding polygalacturonase-inhibiting protein (PGIP) from mature apple fruit has been cloned and characterized. The open reading frame encodes a polypeptide of 330 amino acids, in which 24 amino acids at the N-terminus comprise the signal peptide. Apple PGIP contains 10 imperfect leucine-rich repeat sequence motifs averaging 24 amino acids in length. In addition to the 1.3 kb PGIP transcript, the cloned cDNA also hybridized to RNA molecules with sizes of 3.2 and 5.0 kb. Genomic DNA analysis revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…We have confirmed that orthologs of ZAT10 and ZAT12 are expressed at high levels in ANT samples of C. quitensis experiencing various environmental stresses and presume that the expression of these genes will help maintain intracellular homeostasis in response to environmental stress. In addition, an E3-ligase, ring finger proteins, a PGIP protein and various kinds of transporter proteins, which have been reported to be involved in modulation of abiotic stress responses by posttranslational modification, inhibiting of ice-recrystallization or transport of metabolites 47 , 60 , 61 , were also highly expressed in ANT samples, and expression was induced by cold stress as well. It should be noted that we selected genes that are known to be commonly expressed in the early stages of various stress reactions, and we found that they have higher levels of transcripts in ANT samples that have undergone environmental stress such as low-temperature, high salt, drought, or high UV.…”
Section: Discussionmentioning
confidence: 99%
“…We have confirmed that orthologs of ZAT10 and ZAT12 are expressed at high levels in ANT samples of C. quitensis experiencing various environmental stresses and presume that the expression of these genes will help maintain intracellular homeostasis in response to environmental stress. In addition, an E3-ligase, ring finger proteins, a PGIP protein and various kinds of transporter proteins, which have been reported to be involved in modulation of abiotic stress responses by posttranslational modification, inhibiting of ice-recrystallization or transport of metabolites 47 , 60 , 61 , were also highly expressed in ANT samples, and expression was induced by cold stress as well. It should be noted that we selected genes that are known to be commonly expressed in the early stages of various stress reactions, and we found that they have higher levels of transcripts in ANT samples that have undergone environmental stress such as low-temperature, high salt, drought, or high UV.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, LRR are characteristic components of proteins which are known to be involved in pathogen signal perception and their induction by pathogen elicitors has been reported [27]. The possible involvement of PGIPs in cell signalling has also been reported [28,29]. Apospory is a form of gametophytic apomixis, a unique mode of reproduction whereby plants propagate themselves clonally through seeds [30].…”
Section: Chitosan Elicitor Induce Changes In the Arabidopsis Cell Walmentioning
confidence: 99%
“…Previous studies examining PGIPs from a variety of plant species have indicated that PGIP genes are expressed in various organs and tissues and inferred that the observed organ-specific distribution plays an important role in biotic resistance during plant growth and development ( De Lorenzo and Ferrari, 2002 ; Gomathi et al, 2006 ). Some reports have indicated that PGIPs are mostly expressed in tomato ( Powell et al, 2000 ), apple ( Yao et al, 1999 ), raspberry ( Johnston et al, 1993 ) and strawberry ( Di et al, 2006 ) fruit tissues. However, other reports have shown that PGIPs expression is most abundant in young leaves and less in mature leaves ( Abu-Goukh et al, 1983 ; Johnston et al, 1993 ; Hu et al, 2012 ), while ginseng PGIP are highly expressed in the roots ( Sathiyaraj et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…PGIPs from European pear ( Stotz et al, 1993 ), apple ( Yao et al, 1999 ), Japanese’s pear ( Faize et al, 2003 ), Chinese cabbage-pak-choi ( Huang et al, 2011 ; Liu et al, 2007 ) and poplar ( Cheng et al, 2008 ) are all part of a gene cluster. So far, more than seven PGIPs have been isolated from pepper ( Wang et al, 2013 ), which suggests that PGIP polymorphisms are present in tobacco.…”
Section: Discussionmentioning
confidence: 99%